The impact of climate changes on the ranges of invertebrates (Diptera, Molluska) in Tavush province of Armenia - V. S. Hovhannisyan; L. S. Mirumyan; A. S. Gasparyan; L. G. Avanesyan; S. A. Shogheryan; M. Z. Magomedova; P. D. Magomedova; L. D. Harutyunova (Юг России: экология, развитие, 2023)
Aim. The work’s aim is to study the species composition of invertebrates (Insecta, Molluska) of the Tavush province of Armenia and changes of their ranges due to climatic conditions.Material and Methods. Our own collections of 2021–2022 from different areas of the Tavush province and the collections of invertebrates of the Scientific Centre of Zoology and Hydroecology served as study material. The collection and identification of dipterous insects and mollusks was carried out according to generally accepted methods. The work was performed at the Scientific Centre of Zoology and Hydroecology The scientific material is stored in the collection fund of the Scientific Centre.Results. As a result of our studies of invertebrate species composition, 28 species of horseflies (Tabanidae) are currently listed for the Tavush region: 27 species of phytophagous gall midges (Cecidomyiidae) and 10 species of mollusks. As a result of warming climate change new changes of locality have been registered for: 6 horsefly species S. (N.) caucasicus, Ch. (H.) f. flavipes, Ch. ludens, T. unifasciatus, T. indrae vappa, T. miki; 4 phytophagous gall midge species A. verbasci, D. tortrix, S. euphorbiae, R. terminalis; For one species of mollusk, H. buchi, there are new localities. All these species have expanded their habitat: in horseflies, changes in the range along vertical zonality are observed.Conclusions. As a result of this research, it was revealed that as a consequences of climate change, the ranges of some species of invertebrates – horseflies, gall midges‐phytophages and mollusks – have expanded compared to the data of previous years. All species in which there is a direct dependence of range change on climatic conditions can be further considered as bioindicators of climate change.